Helical Packing of Nanoparticles Confined in Cylindrical Domains of a Self‐Assembled Block Copolymer Structure1. Issue 34 (2nd July 2014) - Sanwaria, Sunita; Horechyy, Andriy; Wolf, Daniel; Chu, Che‐Yi; Chen, Hsin‐Lung; Formanek, Petr; Stamm, Manfred; Srivastava, Rajiv; Nandan, Bhanu
Abstract Theoretical models predict that a variety of self‐assembled structures of closely packed spherical particles may result when they are confined in a cylindrical domain. In the present work we demonstrate for the first time that the polymer‐coated nanoparticles confined in the self‐assembled cylindrical domains of a block copolymer pack in helical morphology, where we can isolate individual fibers filled with helically arranged nanoparticles. This finding provides unique possibilities for fundamental as well as application‐oriented research in similar directions.